Sharia Banking Ownership Status in Performing its Functions as an Intermediation Institution - Setiawan, Iwan; Saruchi, Sarah Athirah Binti (Jurnal Ilmiah Al-Syir'ah, 2024)
This research will discuss the use of third-party funds by Sharia banks as business capital, one of the largest sources of capital for Sharia banks. The use status of these funds is influenced by the contract used, whether full ownership rights or temporary ownership. This research focuses on understanding the status of fund ownership in Sharia banking and its function as an intermediation institution. This research uses a descriptive literature method with a normative juridical approach; the primary data source comes from statutory regulations and the DSN-MUI Fatwa. The type of research used is qualitative research with data analysis techniques carried out in three stages: data focusing, presentation of funds, and drawing conclusions.   This research indicates that the status of fund ownership for Sharia banks has significant implications for the role of Sharia banking as an intermediation institution. Fund ownership status is influenced by the contract used. These contracts will determine the responsibilities of Sharia banks in managing funds. This is based on the provisions of the DSN-MUI Fatwa and the Sharia Banking Law. A clear understanding of the status of fund ownership will help Islamic banks prepare accurate and transparent financial reports, which is essential for building customer and investor trust. Sharia principles ' management of fund ownership status is crucial for Sharia compliance and operational efficiency, risk management, and sustainable growth of Sharia banks as financial intermediation institutions.